Design of a Vernier Permanent Magnet Wind Generator - Dudley, Darren Richard (Department of Electrical Engineering, 2021)
The rise in popularity of renewable energy solutions, in particular wind energy systems, has resulted in a greater demand for low-speed direct-drive machines. The Vernier machine has inherent properties such as high torque density, sinusoidal induced voltages and low torque ripple which makes it suitable for low-speed direct-drive wind applications. Additionally, its mechanical structure is as simple as a conventional permanent magnet (PM) machine, whilst eliminating the need for a mechanical gearbox. The research problem addressed by this dissertation relates to the assessment of the Vernier permanent magnet (VPM) machine topology for direct-drive wind applications. It aims to outline a sizing, detailed design and analysis approach for a three-phase VPM wind generator. Furthermore, a comparative study is conducted using two different rotor types and two different stator types, namely; spoke-type and surface-mounted and fractional slot and integral slot respectively. Vernier theory is used to size the designs after which 2D Finite Element Analysis (FEA) simulations are used to analyse and validate the designs. The main outcome of the comparative study is an assessment of the suitability of four topologies for the direct-drive wind application. The design is assessed on parameters which are critical for wind turbine functionality; namely efficiency, torque ripple, torque density and material consumption. The most suitable of the topologies is selected for prototyping. The rotor is made more robust by adding structural features which mechanically secure laminations and PMs to the shaft. The FEA analysis of the prototype showed favourable performance characteristics, albeit with a small cost in power density. The prototype was -thus manufactured with further mechanical reinforcements made to the bearing system. Experimental results reveal the presence of a defect in the windings. Parameters which are dependent on the winding design are much lower than the analytical and FEA values. These parameters include resistance, inductance, and back-EMF. Further work should look into determining the root cause of the prototype defects.